Long non‐coding RNA (lncRNA) H19 induces hepatic steatosis through activating MLXIPL and mTORC1 networks in hepatocytes. Issue 2 (6th December 2019) - Wang, Hao; Cao, Youde; Shu, Liqing; Zhu, Ying; Peng, Qi; Ran, Longke; Wu, Jinghong; Luo, Yetao; Zuo, Guowei; Luo, Jinyong; Zhou, Lan; Shi, Qiong; et al.
Abstract: Liver plays an essential role in regulating lipid metabolism, and chronically disturbed hepatic metabolism may cause obesity and metabolic syndrome, which may lead to non‐alcoholic fatty liver disease (NAFLD). Increasing evidence indicates long non‐coding RNAs (lncRNAs) play an important role in energy metabolism. Here, we investigated the role of lncRNA H19 in hepatic lipid metabolism and its potential association with NAFLD. We found that H19 was up‐regulated in oleic acid‐induced steatosis and during the development of high‐fat diet (HFD)‐induced NAFLD. Exogenous overexpression of H19 in hepatocytes induced lipid accumulation and up‐regulated the expression of numerous genes involved in lipid synthesis, storage and breakdown, while silencing endogenous H19 led to a decreased lipid accumulation in hepatocytes. Mechanistically, H19 was shown to promote hepatic steatosis by up‐regulating lipogenic transcription factor MLXIPL. Silencing Mlxipl diminished H19‐induced lipid accumulation in hepatocytes. Furthermore, H19‐induced lipid accumulation was effectively inhibited by PI3K/mTOR inhibitor PF‐04691502. Accordingly, H19 overexpression in hepatocytes up‐regulated most components of the mTORC1 signalling axis, which were inhibited by silencing endogenous H19. In vivo hepatocyte implantation studies further confirm that H19 promoted hepatic steatosis by up‐regulating both mTORC1 signalling axis and MLXIPL transcriptional network. Collectively, these findings strongly suggest that H19 may play an important role in regulating hepatic lipid metabolism and may serve as a potential therapeutic target for NAFLD.